co2, ABSORPTION FROM NATURAL GAS USING PIPERAZINE PROMOTED 2-AMIN0-2-METHYL-I-PROPANOL SOLVENT AT HIGH PRESSURE CONDITIONS - ABDUL HALIM, HAIRUL NAZIRAH (2016)
C02 absorption for use in the bulk removal of C02 from C02-rich natural gas (NG) was studied using an alternative absorbent: Piperazine (PZ) promoted 2-Amino- 2-Methyi-1-Propanol (AMP) blended solution. The absorption experiments were conducted in a bench-scale absorption column packed with Sulzer metal gauze packing. The process performance of the alternative absorbent was compared with the MEA solution as a bench-marking absorbent at various operating pressures in the range of 0.10 to S.OS MPa. The performances of the C02 absorption at high C02 partial pressure conditions were evaluated in terms of C02 removal efficiency and the overall volumetric mass transfer coefficient for the gas phase based on unit mol fraction driving force (K}a,). The influence of process parameters was studied for the effects of C02 concentration in NG (30 - SO%), total gas flow rates (33 - SO kmol/m2 h), liquid flow rates (2.89- 4.33 m3/m2.h), amine concentration (20 - SO wt.%) and inlet temperature of liquid (303- 318 K).